Design and Development of Light Weight Engine Mounting for UTeM Formula Varsity Race Car - Rahmat, Mohd Sabirin; Ahmad, Fauzi; Mansor, Muhd Ridzuan; Mat Yamin, Ahmad Kamal; tamaldin, noreffendy (Trans Tech Publications, 2014)
This manuscript provides the design of the engine mounting for Formula Varsity Race Car. Several concept designs were generated for the engine mounting and the final design was selected through in 3D modeling software namely CATIA V5 CAD software during the design phase in this project. The aluminum Alloy 6061 T6 was selected as the lightweight engine mounting material due to high strength, light weight and versatility with many manufacturing processes. The light weight engine mounting was analyzed using finite element analysis in bending and yield strength cases. The result of the engine mounting analysis showed that the engine mounting is able to perform safely as per design requirement.